Americans do I.T. better US multinationals and the productivity miracle - Bloom, Nicholas 1973-; Sadun, Raffaella; Van Reenen, John 1965- (National Bureau of Economic Research, 2007)
The US has experienced a sustained increase in productivity growth since the mid-1990s, particularly in sectors that intensively use information technologies (IT). This has not occurred in Europe. If the US "productivity miracle" is due to a natural advantage of being located in the US then we would not expect to see any evidence of it for US establishments located abroad. This paper shows in fact that US multinationals operating in the UK do have higher productivity than non-US multinationals in the UK, and this is primarily due to the higher productivity of their IT. Furthermore, establishments that are taken over by US multinationals increase the productivity of their IT, whereas observationally identical establishments taken over by non-US multinationals do not. One explanation for these patterns is that US firms are organized in a way that allows them to use new technologies more efficiently. A model of endogenously chosen organizational form and IT is developed to explain these new micro and macro findings.